2017
DOI: 10.1021/acsmedchemlett.7b00058
|View full text |Cite
|
Sign up to set email alerts
|

Carbamylmethyl Mercaptoacetate Thioether: A Novel Scaffold for the Development of L1 Metallo-β-lactamase Inhibitors

Abstract: Given the clinical importance of metallo-β-lactamases (MβLs), a new scaffold, N-substituted carbamylmethyl mercaptoacetate thioether, was constructed. The obtained molecules - inhibited MβLs from all three subclasses, but preferentially L1 from subclass B3. Compound with a-carboxyphenyl substituent exhibited the broadest spectrum with at least 70% inhibition of enzymes from all subclasses at 100 μM, while compound with a-methylphenyl substituent was the most potent inhibitor of any individual enzyme, with 97% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…133,134 Substituted amide derivatives of mercaptoacetic acid (mercaptoacetamides, 41) are also prominent in a number of recent studies: Arjomandi and co-workers reported a series of amino acid conjugates of mercaptoacetamide and some longer chain homologs (mercaptpropionamide and mercaptobutyramide) which display IMP-1 inibition. 135 Other studies employed mercaptoacetamide thioethers containing acetate 136 and azolyl ring [137][138][139][140] substituents. The diverse library of thiolcontaining MBL-inhibitors also include thiomethylbenzoic acids, 141 bisthiazolidines, 142,143 rhodanines and its related thioenolates, [144][145][146][147] cysteine-containing oligopeptides, 148,149 phosphonate and tetrazole bioisosters of mercaptoacids 150 and thiones.…”
Section: Recent Advances In the Development Of Mbl Inhibitorsmentioning
confidence: 99%
“…133,134 Substituted amide derivatives of mercaptoacetic acid (mercaptoacetamides, 41) are also prominent in a number of recent studies: Arjomandi and co-workers reported a series of amino acid conjugates of mercaptoacetamide and some longer chain homologs (mercaptpropionamide and mercaptobutyramide) which display IMP-1 inibition. 135 Other studies employed mercaptoacetamide thioethers containing acetate 136 and azolyl ring [137][138][139][140] substituents. The diverse library of thiolcontaining MBL-inhibitors also include thiomethylbenzoic acids, 141 bisthiazolidines, 142,143 rhodanines and its related thioenolates, [144][145][146][147] cysteine-containing oligopeptides, 148,149 phosphonate and tetrazole bioisosters of mercaptoacids 150 and thiones.…”
Section: Recent Advances In the Development Of Mbl Inhibitorsmentioning
confidence: 99%
“…McGeary synthesizes a series of 2‐aminopyrrole‐1‐benzyl‐4,5‐diphenyl‐1H‐pyrrole‐3‐carbonitrile derivatives that can inhibit MBLs extensively as a good example (). Finally, some thioesters and ester thioethers, as well as thione derivatives, have recently been reported, some of which also show broad‐spectrum inhibition of related MBLs (Chang et al., ; Liu, Shi, Kang, Oelschlaeger, & Yang, ; Sevaille et al., ).…”
Section: Progress In Designing Metallo‐β‐lactamase Inhibitorsmentioning
confidence: 99%
“…The metal-chelating thioether-based MBL inhibitor ( 34 ; Fig. 5 ; IC 50 value of 0.41 µM against L1 MBL) has been reported 137 to restore the antimicrobial properties of cefazolin to that of susceptible, non–MBL-producing E. coli cells. Virtual screening methodologies 138,139 have also been applied for identification of non–β-lactam BML inhibitors, including nonmetal chelating structures, in addition to the use of a recombinant NDM-1 strategy.…”
Section: Old Structures: Delaying the Amrmentioning
confidence: 99%